2004
DOI: 10.1016/j.jbankfin.2003.10.018
|View full text |Cite
|
Sign up to set email alerts
|

On the way to recovery: A nonparametric bias free estimation of recovery rate densities

Abstract: In this paper we analyse recovery rates on defaulted bonds using the Standard and Poor's / PMD database for the years 1981-1999. Due to the speci…c nature of the data (observations lie within 0 and 1), we must rely on nonstandard econometric techniques. The recovery rate density is estimated nonparametrically using a beta kernel method. This method is free of boundary bias, and Monte Carlo comparison with competing nonparametric estimators show that the beta kernel density estimator is particularly well suited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…On the contrary, our parametric model cannot exhibit local modes in the interval (0,1), as many empirical studies have shown (e.g., ). For this reason, a future development of the model, here proposed, could be to assume that the continuous part of the recovery rate is a mixture of beta random variables.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…On the contrary, our parametric model cannot exhibit local modes in the interval (0,1), as many empirical studies have shown (e.g., ). For this reason, a future development of the model, here proposed, could be to assume that the continuous part of the recovery rate is a mixture of beta random variables.…”
Section: Introductionmentioning
confidence: 62%
“…Most empirical research focuses on modeling and estimating default probabilities, whereas only recently, the recovery analysis is attracting attention. Several studies consider recovery rates on corporate bonds (e.g., ), whereas some authors deal with bank loans (e.g., ). Because loans are private instruments, few data are available.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Alternatives in the literature having different advantages and disadvantages relative to our approach, which we find to yield similar results on this dataset, include non-parametric approaches (Renault and Scailett [2003]) or maximumentropy (Friedman and Sandow [2003]). …”
Section: Econometric Modelingmentioning
confidence: 63%
“…As competitors of the models in our family we consider some of the non‐parametric approaches for density estimation discussed in Section 2. They are (a)GK, the Gaussian kernel that was considered by Renault and Scaillet () and Chen and Wang (), (b)H‐BK, the semiparametric density that was considered by Hagmann et al . (), (c)C‐BK, the beta kernel that was introduced by Chen (), and applied by Renault and Scaillet (), and (d)CZ‐BK, the beta kernel that was proposed by Calabrese and Zenga (). …”
Section: Real Data Analysismentioning
confidence: 99%